The Impact of COVID-19-Related Measures on the Solar Resource in Areas with High Levels of Air Pollution - Peters, Ian Marius; Brabec, Christoph; Buonassisi, Tonio; Hauch, Jens; Nobre, André M. (Joule, 2020)
Restrictions enacted to reduce the spreading of COVID-19 have resulted in notably clearer skies around the world. In this study, we confirm that reduced levels of air pollution correlate with unusually high levels of clear-sky insolation in Delhi, India. Restrictions here were announced on March 19th, with the nation going into lockdown on March 24th. Comparing insolation data before and after these dates with insolation from previous years (2017 to 2019), we observe an 8.3% ± 1.7% higher irradiance than usual in late March and a 5.9% ± 1.6% higher one in April, while we find no significant differences in values from previous years in February or early March. Using results from a previous study, we calculated the expected increase in insolation based on measured PM2.5 concentration levels. Measurements and calculations agree within confidence intervals, suggesting that reduced pollution levels are a major cause for the observed increase in insolation. A broadly noticed consequence of the restrictions enacted to counter the spreading of COVID-19 was unusually clear skies in many regions of the world. Better air quality has an impact on solar power generation, as fewer pollution particles in the air means that more sunlight will reach solar panels on the ground. In this study, we explore how air pollution in Delhi has developed following the lockdown on March 24th and how this reduction has affected how much sunlight the city received. First, we looked at measured particle concentration levels and noticed that after lockdown, levels dropped to about half of where they had been in previous years. Then, we looked at how much sunlight was received by solar panels. Before lockdown, insolation was similar to previous years. Yet, after lockdown, there was a clear and significant increase. In late March, insolation was up by 8.3% compared with levels in previous years. This is comparable to moving a solar panel from Toronto to Houston. Following restrictions to counter the spread of COVID-19, reports about unusually clear skies appeared in many regions of the world. In this study, we explore how air pollution in Delhi has developed following the lockdown on March 24th and how this reduction has affected how much sunlight the city received. Until early April, pollution levels had dropped to half of their usual levels. The cleaner air allowed more sunlight to pass, increasing insolation by more than 8%.
CRIS-Team Scopus Importer:2020-07-24
Keywords: air pollution; COVID-19; solar energy